The Mantra of “Dare to Fight" As a Confucian Value in Xi’s Foreign Policy - Aurelia, Angel (Jurnal Ilmiah Widya Sosiopolitika, 2024)
Confucianism is a philosophy and belief system that has deeply influenced Chinese culture. As the time goes by, China is still embodies Confucian values in its political moves. One significant move is on their newest foreign policy mantra with the point “Dare to Struggle “which differs from Deng’s mantra and more diplomatic. This research uses quantitative analysis with descriptive method to describe how China still uses Confucianism in their political move. “Dare to Struggle “ point has matched with Yi  and Zhi values.